2020
DOI: 10.1038/s41467-020-18640-0
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular correlates of cisplatin-based chemotherapy response in muscle invasive bladder cancer by integrated multi-omics analysis

Abstract: Overtreatment with cisplatin-based chemotherapy is a major issue in the management of muscle-invasive bladder cancer (MIBC), and currently none of the reported biomarkers for predicting response have been implemented in the clinic. Here we perform a comprehensive multi-omics analysis (genomics, transcriptomics, epigenomics and proteomics) of 300 MIBC patients treated with chemotherapy (neoadjuvant or first-line) to identify molecular changes associated with treatment response. DNA-based associations with respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
117
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(126 citation statements)
references
References 67 publications
5
117
3
1
Order By: Relevance
“…7a for details), carcinoma cells (pan-cytokeratin, CK5/6, and GATA3) and immune recognition/escape mechanisms (PD-L1 and MHC class I). Automated image analysis algorithms 41 were applied to study the spatial organization of immune cells and immune evasion mechanisms (Fig. 4a and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…7a for details), carcinoma cells (pan-cytokeratin, CK5/6, and GATA3) and immune recognition/escape mechanisms (PD-L1 and MHC class I). Automated image analysis algorithms 41 were applied to study the spatial organization of immune cells and immune evasion mechanisms (Fig. 4a and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Gene-expression-based molecular subtypes were reported to be associated with survival in platinum-treated MIBC patients [ 8 ]. However, other authors could not confirm this observation [ 9 ]. Therefore, prediction of survival for patients who receive platinum-based chemotherapy remains an unmet clinical need.…”
Section: Introductionmentioning
confidence: 82%
“…In the last years, several potential therapy-predictive markers, such as the excision repair gene ERCC1 , HMGA2 , nucleoside transporter protein hENT1, transcription factor TFAP, apoptosis inhibitor surviving, EMMPRIN and SDC1, have been identified [ 28 , 29 , 30 , 31 , 32 ]. In addition, gene-expression-based molecular subtypes of MIBC were suggested to show different sensitivities to platinum therapy [ 8 , 9 ]. However, currently, none of these markers has become established in routine clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Third, bulk RNA-seq and microarray GE data are confounded by signals from a mixture of cell populations, making it necessary to collaborate these RNA-based findings with multiplex immunohistochemistry to investigate tumor cell intrinsic changes and its crosstalk with the immune and stromal microenvironments that dictate therapy response. Finally, we are aware that a recent study using the consensus classification method in a different patient cohort revealed basal/squamous tumors exhibited a poor response to chemotherapy 62 . It is unclear if these findings are related to previous functional studies showing basal cancer stem cell repopulation is a contributing driver to chemoresistance 63 .…”
Section: Discussionmentioning
confidence: 99%